KARAKTERISTIK ḌABṬ MUSHAF NUSANTARA: Kajian Analitis Komparatif Terhadap Mushaf Standar Indonesia Dan Mushaf Pojok Menara Kudus - Alwi, Wildan; Sipahutar, Rahmat Taufik (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2024)
This study aims to describe the differences and similarities of ḍabṭ and the factors that influence both of them which are affixed to the Indonesian Standard Mushaf (hereinafter abbreviated as MSI) and the Pojok Menara Kudus Mushaf (hereinafter abbreviated as MPMK). This study uses a qualitative method and the data in this study were obtained through library research by collecting data from circulating mushafs to obtain significant results. This study concludes that the study of Ḍabṭ science (harakat and punctuation) is very important in the journey of changes in the Al-Qur'an mushaf and its early circulation in the archipelago in the 19th century, at least two popular mushafs circulated, namely Bahriyah and Bombay which became the forerunners of MSI and MPMK, both mushafs were familiar to the consumption of Indonesian Muslim society before standardization, until finally in 1984 the standardization of mushafs became an important reference regarding the legality of the circulation of mushafs in the archipelago